2020
DOI: 10.1016/j.nicl.2020.102430
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain damage and visual disorders in children with cerebral palsy due to periventricular leukomalacia

Abstract: Highlights There is a strong correlation between brain lesion severity and visual function, evident also with a Structural MRI. It is confirmed the validity of MRI semi-quantitative scale published by Fiori et al. (2014). There is a frequent association of PVL with thalamic lesions with important repercussion on visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 29 publications
1
37
3
Order By: Relevance
“…Intermediate disorders include tunnel/tubular vision (i.e., concentric reduction of the visual field), or its opposite, retention of peripheral vision (i.e., loss of the central visual field, while the peripheral visual field is preserved), homonymous lateral hemianopia (i.e., loss of the contralesional visual field), or quadrantanopia (i.e., loss of a visual quadrant). Lower visual field impairment due to periventricular leukomalacia (often associated with premature birth or CP) can be peripheral or complete, or manifest as degraded clarity in the lower visual fields (Jacobson et al, 2006;Tinelli et al, 2020), and it can be combined with dorsal stream dysfunction, leading to a major deficit in global visual processing. These different disorders may exist as such or be observed successively in the same patient who may show a degree of recovery over time (Guzzetta et al, 2001b;Watson et al, 2007;Werth, 2008).…”
Section: Patterns Of Cortical or Cerebral Visual Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermediate disorders include tunnel/tubular vision (i.e., concentric reduction of the visual field), or its opposite, retention of peripheral vision (i.e., loss of the central visual field, while the peripheral visual field is preserved), homonymous lateral hemianopia (i.e., loss of the contralesional visual field), or quadrantanopia (i.e., loss of a visual quadrant). Lower visual field impairment due to periventricular leukomalacia (often associated with premature birth or CP) can be peripheral or complete, or manifest as degraded clarity in the lower visual fields (Jacobson et al, 2006;Tinelli et al, 2020), and it can be combined with dorsal stream dysfunction, leading to a major deficit in global visual processing. These different disorders may exist as such or be observed successively in the same patient who may show a degree of recovery over time (Guzzetta et al, 2001b;Watson et al, 2007;Werth, 2008).…”
Section: Patterns Of Cortical or Cerebral Visual Impairmentmentioning
confidence: 99%
“…Children with CVI are frequently observed to have oculomotor disorders, difficulties in visual fixation or visual pursuit, hypometric saccades, or a disorder of gaze strategy ( Stiers et al, 2002 ; Fazzi et al, 2004 ), as well as nystagmus due to periventricular leukomalacia ( Jacobson et al, 1998 ; Tinelli et al, 2020 ). These conditions are associated with reduced visual performance.…”
Section: The Differences Between Typical Vision and Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
“…Performance on a task of global motion coherence was associated with integrity of the right superior longitudinal fasciculus in typically sighted children ( Braddick et al, 2016 ) and white matter connections of the visual cortex to temporal cortex in people with CVI ( Pamir et al, 2021 ). Using the coding template for MRI brain scans ( Fiori et al, 2014 ), brain damage scores of global structural, hemispheric and subcortical scores were found to correlate significantly with basic vision disorder in children with cerebral palsy and periventricular leukomalacia ( Tinelli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With advances in perinatal care, the survival rates of infants with hypoxic-ischemic encephalopathy have increased ( Lee et al, 2013 ). Up to 60% of infants who survive have severe disabilities, including intellectual disability, epilepsy, and cerebral palsy ( Pierrat et al, 2005 ); however, hypoxic-ischemia (HI) is also a major cause of acquired visual impairment in children from developed countries ( Tinelli et al, 2020 ). Although cortical visual dysfunction is an important cause of visual impairment, our previous studies demonstrated that the immature retina is also susceptible to HI injury ( Huang et al, 2012 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%